Neurophysiological indices for split phenomena: correlation with age and sex and potential implications in amyotrophic lateral sclerosis - Zoccolella, Stefano; Milella, Giammarco; Giugno, Alessia; Devitofrancesco, Vito; Damato, Rosaria; Tamburrino, Ludovica; Misceo, Salvatore; Filardi, Marco; Logroscino, Giancarlo (Frontiers in Neurology, 2024)
Background. Split phenomena (SP) are characterized by patterns of differential muscle wasting and atrophy, which are highly prevalent in Amyotrophic lateral sclerosis (ALS) patients. Several neurophysiological indicators, including the split-hand index (SHI), split-leg index (SLI), and splitelbow index (SEI), have been proposed to assess SP. Nevertheless, their cut-off values and the impact of age and sex on these measures remain unclear.Methods. We prospectively collected neurophysiological data from 300 healthy adult subjects. The following indexes were computed from compound muscle action potentials (CMAPs): SHI [abductor pollicis brevis (APBcmap) x first dorsal interosseous (FDI)cmap/adductor digiti minimi (ADMcmap)], SEI (BICEPScmap/TRICEPScmap), SLI (extensor digit brevis (EDB)cmap/abductor Hallucis (AH)cmap) and the neurophysiological ratios APBcmap /ADMcmap and FDIcmap/ADMcmap. Multiple linear regression analysis was used to investigate the association between age, sex, CMAPs, and neurophysiological indicators.Results. The median SHI was 10.4, with median APBcmap/ADMcmap ratio of 0.9 and median FDIcmap/ADMcmap ratio of 1.2. The median SEI was 1.6 (IQR:1.1-2.4) and median SLI was 0.7 (IQR:0.5-1.0). Negative associations were observed between age and most of the CMAPs and all the neurophysiological indices, except for SLI. Male subjects exhibited significantly higher values of CMAP of FDI and biceps and SHI compared to females. Conclusions. Our findings highlight the importance of age and sex-adjusted normative data for SP indexes, which could enhance their diagnostic accuracy and clinical utility in patients with ALS. SL index appears to be the most reliable indicator, as it showed no significant association with age or sex.